Late recurrent gastric carcinoma 12 years after surgery with attenuation of CD44 variant 9 expression - Hirokatsu Hayashi; Itaru Yasufuku; Toshiya Higashi; Wakana Chikaishi; Ryoma Yokoi; Masahiro Fukada; Yuta Sato; Ryuichi Asai; Jesse Yu Tajima; Chiemi Saigo; Akitaka Makiyama; Yoshihiro Tanaka; et al. (Surgical Case Reports)
Abstract Background Late recurrence of gastric cancer at 10 years post-gastrectomy is extremely rare, and the underlying mechanism remains unclear. We report a para-aortic lymph node metastasis case that recurred 12 years postoperatively. Case presentation A 44-year-old woman pathologically diagnosed with moderately to poorly differentiated adenocarcinoma with pT2(SS)pN2cM0pStageIIIA according to the Japanese Classification of Gastric Carcinoma (the 13th Edition) underwent laparoscopic distal gastrectomy with D1 + lymph node dissection. She received adjuvant chemotherapy with tegafur-uracil (400 mg/day) for 2 years. At postoperative year (POY) 5, a swollen lymph node was detected in the No.16b1lat lymph node station. However, positron emission tomography (PET) revealed normal uptake, and the levels of tumor markers were within normal limits; hence, the possibility of metastasis was considered low, and the patient was placed under observation. At POY 12, computed tomography revealed an enlargement of the No.16b1lat lymph node station, and PET showed abnormal uptake. Endoscopic ultrasound-guided fine-needle aspiration revealed a moderately differentiated adenocarcinoma. Hence, a diagnosis of recurrence of gastric cancer was made. The patient underwent para-aortic nodal dissection (PAND) of No.16b1lat & int stations. Immunochemical staining results also suggested the recurrence of gastric cancer. However, the expression of CD44 variant 9 (CD44v9), a cancer stem cell marker for gastric adenocarcinoma, was attenuated in the recurrent lesions compared with that in the primary lesions. Postoperatively, she received chemotherapy with tegafur–gimeracil–oteracil (80 mg/day) for 1 year. Bone metastasis was observed at POY 4 after PAND, and the IHC analysis showed a HER2 score of 3 + in a needle biopsy specimen of bone metastasis. The expression of CD44v9 was slightly positive. The patient is being treated with chemotherapy with FOLFOX + trastuzumab. Conclusions A defense mechanism against reactive oxygen species has been reported as a mechanism causing recurrence of CD44v9-positive gastric cancer. Consequently, CD44v9-positive gastric cancer grows in metastatic organs, repeatedly self-renews, and proliferates to form recurrent lesions. In the present case, the degree of CD44v9 staining in recurrent lesions was suggested to be related to the recurrence time.